The effects of essential oil from Lippia origanoides and herbal betaine on performance, intestinal integrity, bone mineralization and meat quality in broiler chickens subjected to cyclic heat stress - Señas-Cuesta, Roberto; Stein, Andressa; Latorre, Juan D.; Maynard, Clay J.; Hernandez-Velasco, Xochitl; Petrone-Garcia, Victor; Greene, Elizabeth S.; Coles, Makenly; Gray, Latasha; Laverty, Lauren; Martin, Kristen; Loeza, Ileana; et al. (Frontiers in Physiology, 2023)
Essential oils (EO) affect performance, intestinal integrity, bone mineralization, and meat quality in broiler chickens subjected to cyclic heat stress (HS). Day-of-hatch Cobb 500 male broiler chicks (n=475) were randomly divided into four groups. Group 1: No heat stress (Thermoneutral) + control diets with no antibiotics; Group 2: heat stress control + control diets; Group 3: heat stress + control diets supplemented with thymol chemotype (45 ppm) and herbal betaine (150 ppm) formulation EO1; Group 4: heat stress + control diets supplemented with phellandrene (45 ppm) and herbal betaine (150 ppm) formulation EO2. From day 10 to 42, the heat stress groups were exposed to cyclic HS at 35°C for 12 hours (8:00–20:00). BW, BWG, FI, and FCRc were measured at d 0, 10, 28, and 42. Chickens were orally gavaged with FITC-d on days 10 (before heat stress) and 42. Morphometric analysis of duodenum and ileum samples and bone mineralization of tibias were done. Meat quality was assessed on day 43 with ten chickens per pen per treatment. Heat stress reduced BW by day 28 (P < 0.05) compared to thermoneutral chickens. At the end of the trial, chickens that received both formulations of EO1 and EO2 had significantly higher BW than HS control chickens. A similar trend was observed for BWG. FCRc was impaired by EO2 supplementation. There was a significant increase in total mortality in EO2 compared with EO1 EO1 chickens had lower FITC-d concentrations at day 42 than the HS control. In addition, EO1 treatment is not statistically different if compared to EO2 and thermoneutral. Control HS broilers had significantly lower tibia breaking strength and total ash at day 42 than heat-stressed chickens supplemented with EO1 and EO2. Heat stress affected intestinal morphology more than thermoneutral chickens. EO1 and EO2 improved intestinal morphology in heat-stressed chickens. Woody breast and white striping were more common in thermoneutral chickens than heat stress chickens. In conclusion, the EO-containing diet could improve broiler chicken growth during cyclic heat stress, becoming increasingly relevant in antibiotic-free production in harsh climates.